A Simplified 2D Heart Model of the Wolff-Parkinson-White Syndrome. Issue 26 (2016) - Zeile, Clemens; Scholz, Eberhard; Sager, Sebastian
Abstract: The enormous progress made in computational cardiac electrophysiology during the past decades has resulted in a diverse range of models and numerical methods. In general, researchers have elaborated highly complex and detailed simulators on the cell and tissue level. In contrast, there has been a lack of simplified whole-heart models that study specific heart arrhythmias. In this study, we approximate the electrophysiology of Wolff-Parkinson-White Syndrome with such a model. In order to reproduce the cardiac anomaly, we apply the so-called bidomain approach involving partial differential equations. Results show that the simulations are realistic, both in ECG generation and electric activation sequence. Our assessment of the model implementation takes into account parameter and geometry variation, which supports a realistic view of medical aspects. Our in silico analysis thus helps provide clear insights into the mechanisms of arrhythmias and associated ECG changes.